Chest pain and panic disorder: physical symptom or coronary heart disease presentation? (Archives of Clinical Psychiatry, 2007)
Panic disorder is a mental disorder that belongs to the group of the anxiety disorders, characterized by repeated and unexpected panic attacks, in which the somatic symptoms are associated to intense apprehension related to the idea of "loosing control" or an imminent death sensation. Amongst somatic symptoms that patients can present, chest pain plays an important role, reinforcing the idea that the patient is threatened by a serious cardiovascular problem, leading to repeated search for attendance in cardiologic or other emergency rooms. Myocardial ischemia develops when coronary blood flow becomes inadequate to meet the requirements of the myocardium for oxygen and metabolic substrates to maintain adequate cardiac function. Coronary stenosis is considered the main cause of myocardial ischemia and its most common clinical manifestation is chest pain. This case report illustrates panic disorder co-occurring with coronary heart disease, discussing how to deal with this complex clinical situation. The diagnosis of panic disorder seldom is made and serious consequences can elapse, including the course of the psychiatric disorder.